[18F]NaF PET/CT imaging of response to single fraction SABR to bone metastases from breast cancer - Hardcastle, Nicholas; Liu, Yang; Siva, Shankar; David, Steven (Frontiers in Nuclear Medicine, 2023)
Breast cancer commonly metastasizes to the skeleton, and stereotactic ablative body radiation therapy (SABR) is an emerging treatment for oligometastatic disease. Accurately imaging bone metastases and their response to treatment is challenging. [ 18 F]NaF -PET has higher sensitivity and specificity than conventional bone scans for detecting breast cancer bone metastases. In this pre-defined secondary analysis of a prospective trial, we evaluated change in [ 18 F]NaF uptake after SABR.Patients with oligometastatic breast cancer received a single fraction of 20 Gy to up to three bone metastases. [ 18 F]NaF-PET was acquired before and 12 months after SABR. Pre-and post-treatment [ 18 F]NaF-PET images were registered to the treatment planning CT. The relative change in tumour SUVmax and SUVmean was quantified. The intersection of each of radiation therapy isodose contours with non-tumour bone was created. The change in SUVmean in sub-volumes of non-tumour bone receiving doses from 0-20 Gy was quantified.Fourteen patients, with 17 bone metastases were available for analysis. Fifteen metastases exhibited reduction in SUVmax; the median reduction was 42%, and maximum reduction 82%. Increased absolute reduction in SUVmax was observed with higher pre-treatment SUVmax. One patient exhibited increased SUVmax after treatment, which was attributed to normal peri-tumoral bone regeneration in the context of a bone metastasis. There was a median reduction of 15-34% for non-tumour bone in each dose level.